Alignment of Classroom Instruction with Indonesian National Standards - RUMTINI SUWARNO; EARL VANCE RANDALL; JULIE M HITE (Indonesian Research Journal in Education |IRJE|, 2019)
This study examines the degree of alignment between classroom instruction and national curriculum standards. This alignment may vary as a function of teacher characteristics. Using self-reports from teachers about their experiences teaching the national curriculum standards, the study explores the extent to which classroom instruction aligns with Indonesian national standards in the following nationally-assessed subjects: Indonesian, English, science, and mathematics. A mixed multilevel regression analyses was used to examine the relationships between alignments and teacher characteristics. The study involved 501 junior secondary school teachers from three western provinces in Indonesia (Lampung, Jakarta, and East Java). The findings showed that the majority of teachers taught 100% of the topics outlined in the national curriculum standards. However, a small number of teachers had taught less than 100% of the required topics. In fact, some of them had only taught less than 70%. As the Indonesian educational system used standards-based national exams, skipping topics in classroom instruction may significantly affect student achievement because test items are developed based on the curriculum standards. In terms of the relationships of alignments with teacher characteristics such as gender, working status, college major, level of education, years of teaching experience and professional development, the findings suggested that these relationships varied. Theoretically, this research provides two contributions: (1) lacking research in the area of curriculum standards and classroom instruction as mediator of student competencies, the findings of this study make an important contribution to the current research of the standards-based education system; (2) predicting alignments as a function of teacher characteristics in this study contributes to the theoretical discussion of teacher characteristics and their possible effects on classroom instruction.